Distribution and Temporal Dynamics of Plasmodium falciparum Chloroquine Resistance Transporter Mutations Associated With Piperaquine Resistance in Northern Cambodia. (2nd February 2021) - Shrestha, Biraj; Shah, Zalak; Morgan, Andrew P; Saingam, Piyaporn; Chaisatit, Chaiyaporn; Chaorattanakawee, Suwanna; Praditpol, Chantida; Boonyalai, Nonlawat; Lertsethtakarn, Paphavee; Wojnarski, Mariusz; Deutsch-Feldman, Molly; Adams, Matthew; et al.
Abstract: Background: Newly emerged mutations within the Plasmodium falciparum chloroquine resistance transporter (PfCRT) can confer piperaquine resistance in the absence of amplified plasmepsin II ( pfpm2 ). In this study, we estimated the prevalence of co-circulating piperaquine resistance mutations in P. falciparum isolates collected in northern Cambodia from 2009 to 2017. Methods: The sequence of pfcrt was determined for 410 P. falciparum isolates using PacBio amplicon sequencing or whole genome sequencing. Quantitative polymerase chain reaction was used to estimate pfpm2 and pfmdr1 copy number. Results: Newly emerged PfCRT mutations increased in prevalence after the change to dihydroartemisinin-piperaquine in 2010, with >98% of parasites harboring these mutations by 2017. After 2014, the prevalence of PfCRT F145I declined, being outcompeted by parasites with less resistant, but more fit PfCRT alleles. After the change to artesunate-mefloquine, the prevalence of parasites with amplified pfpm2 decreased, with nearly half of piperaquine-resistant PfCRT mutants having single-copy pfpm2. Conclusions: The large proportion of PfCRT mutants that lack pfpm2 amplification emphasizes the importance of including PfCRT mutations as part of molecular surveillance for piperaquine resistance in this region. Likewise, it is critical to monitor for amplified pfmdr1 in these PfCRT mutants, as increased mefloquine pressure could lead to mutants resistant to both drugs. Abstract : As of 2017, newly emerged piperaquine-resistant PfCRT mutants were nearly fixed in northern Cambodia, with nearly half having single-copy pfpm2 . These results emphasize the importance of including PfCRT mutations in molecular surveillance for piperaquine resistance in this region.